A Metal Chaperone Gene Regulates Rice Growth and Seed Development by Manganese Acquisition and Homeostasis - Chao Li; He Li; Justice Kipkorir Rono; Mong Qi Wang; Zhi Min Yang (Agronomy, 2022)
Manganese (Mn) is a mineral element essential for plant growth and development. In agronomy reality, Mn deficiency or overload in crops disturbs metal homeostasis, photosynthesis, and many other biological processes. Mining genetic resources linking Mn acquisition and homeostasis is vitally important to help understand plant adaptation to Mn stress and breeding genetically improved crops for sustainable agriculture. Metallic chaperone (metallochaperone) is a class of family proteins playing an essential role in positive responses to metal and abiotic stresses. Here, we report a novel function of a metal chaperone gene OsHIPP56 in regulating Mn accumulation in rice (Oryza sativa) crops. OsHIPP56 was transcriptionally induced by excessive Mn stress but hardly by Mn deficiency. OsHIPP56-expression in a yeast Mn-sensitive mutant pmr1 rescued the Mn-defective phenotype by increasing Mn accumulation in cells. Knocking out OsHIPP56 by Crispr/cas9 protocol did not affect the growth and physiological responses of rice seedlings supplied with normal Mn concentration. However, excess Mn stress moderately retarded growth of the knockout plants compared with the wild-type. A life span field trial was conducted under natural conditions with the two rice varieties. Knocking out OsHIPP56 also distorted rice growth, leading to reduced plant height, stem elongation, panicle length, spikelet fertility, seed size, and grain yield. Mn concentrations in rice straw (leaves and stem/internodes), brown rice, and husk in cas9 plants were much lower than those in wild-type. This was particularly seen in the brown rice where the Mn concentrations in cas9 plants were reduced by 26.7–49.1% compared with the wild-type control. Overall, these lines of evidence point out that OsHIPP56 plays a primary role required for rice growth, seed development, and Mn acquisition.